Local Fractional Derivative Boundary Value Problems for Tricomi Equation Arising in Fractal Transonic Flow - Xiao-Feng Niu; Cai-Li Zhang; Zheng-Biao Li; Yang Zhao (Abstract and Applied Analysis)
The local fractional decomposition method is applied to obtain the nondifferentiable numerical solutions for the local fractional Tricomi equation arising in fractal transonic flow with the local fractional derivative boundary value conditions.